Emotions experienced by parents whose children have spinal muscular atrophy: A qualitative research - Simsek, Didem Coskun; Cetin, Kerime Deniz Kilic (Elsevier Science Inc, 2025)
Background: The lifelong and intensive treatment and care process of Spinal Muscular Atrophy may cause a decrease in the life quality of the child and the parents. This study aims to examine the emotions of parents who have a child with Spinal Muscular Atrophy within the framework of a phenomenological design. Methods: This study was conducted with a phenomenological design. The study was carried out between August 2022 and April 2024 with the parents of children treated for Spinal Muscular Atrophy in the pediatric ward of a university hospital. Using a purposive sampling method, 11 parents were involved in interviews. A semi-structured questionnaire was employed during the interviews, and all the interviews were audio recorded. The data analysis done by applying the inductive thematic analysis method. The study was carried out according to the COREQ checklist. Findings: It was found that 54.54% of the children who participated in the study were diagnosed with Spinal Muscular Atrophy between the ages of 0 and 1 year, 72.72 % between 0 and 6 months, and 54.54% were Spinal Muscular Atrophy TYPE 1 patients. As a result of thematic analysis method, five main and ten sub- themes had emerged. These are; (1) helplessness (helplessness of having to accept, helplessness of not being able to spare time), (2) being upset (being upset about the symptoms of the disease, feeling misunderstood, sadness about their healthy children), (3) stress (stress due to the intensive and exhausting treatment and care process, stress due to the economic situation), (4) fear (fear of death, fear of future pregnancies), (5) unhappiness (being unhappy with the changing living conditions). Discussion: It was observed that parents who have a child with Spinal Muscular Atrophy experience emotional challenges. Application to practice: Gaining insights into the perspectives of parents can enable healthcare professionals to better understand the negative emotional experiences of parents caring for children with Spinal Muscular Atrophy. Such understanding may guide the development of targeted strategies to provide comprehensive psychological support aimed at improving parental mental health outcomes. Increasing awareness among healthcare professionals and the broader society fosters a more informed and empathetic approach to addressing the challenges faced by children with Spinal Muscular Atrophy and their families, enhancing the quality of care and support provided. (c) 2024 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Children; Emotions; Parents; Spinal muscular atrophy